Milling of chickpea, lentil, and yellow pea and flowability, rheology, and bread-making properties of the flours - Nkurikiye, Eric (Kansas State University, 2022)
Pulses have excellent environmental adaptability, sustainability, nutritional, and agronomical advantages which have led to increasing consumer interests and global demand recently. The rising need of gluten-free products also contributes to this trend. Since then, the milling and baking industry started to assess the feasibility of integrating pulses into baked foods. So far, there are limited research studies on the application of current grain processing technologies for pulse grains and their baking potentials. This study aimed to develop milling techniques for pulse grains and understand their flowability and bread-making properties when incorporated into refined wheat flour. The first objective was to develop milling processes to produce refined chickpea, lentil, and yellow pea flours with small, medium, and large particle sizes, and assess the bulk and flow properties of the flours. The grains were tempered and then milled using a laboratory roller mill. Three flours of different particle size with similar proximate composition were produced for each pulse grain. Hosokawa powder tester and FT4 powder rheometer equipment were used to determine the flow properties of the pulse flours. Among the pulses, chickpea flours had the lowest bulk and tapped density and the highest aeration ratio. Chickpea flours were found to be very cohesive and more compressible compared to the other pulse flours. For each pulse type, the small-sized flours were more cohesive than the medium and large-sized flours. The medium and large-sized lentil flours showed similar flow properties as the commercial wheat flour used. The second objective was to investigate the effect of pulse flour substitution in refined wheat flour on bread making properties. The lentil, yellow pea, and chickpea flours of different particle size were incorporated into the refined wheat flour at levels of 5, 12.5, and 20% (w/w). Mixograph test was done to determine the optimum water absorption and mixing time. The blends were then baked, and the bread physical properties were tested after baking. It was found that increased of incorporation reduced the bread’s specific volume while increasing the bread hardness. The particle size difference did not significantly affect the qualities of the breads across different incorporation levels. At the same level of pulse incorporation, chickpea-wheat blends produced larger and softer loaves of bread. It was found that at 12.5% pulse incorporation level or lower, the bread qualities are acceptable. Because of the better potential of chickpea for bread-making compared to lentil and yellow pea, we conducted a third study focusing on the dough rheological properties and processibility when incorporating chickpea flour into refined wheat flour. 20 different refined wheat flours of varying protein content and mixing properties were evaluated with chickpea incorporation, and chickpea flours with varying application ratios (0 – 30%), particle sizes (small, medium, large), types (kabuli vs. desi), and fractions were further tested. Mixograph and dough extensibility tests were performed. Sensory study was also conducted for the chickpea-wheat blend breads. Mixograph results showed that chickpea flour consistently increased the dough mixing tolerance of wheat flour when incorporated at 7.5%. For a few flours which were categorized as strong, there was no significant difference between the composite and control flour. Dough extensibility test showed that dough strength was increased significantly when chickpea flour was incorporated at 7.5% or lower. Further fractionation of the chickpea flour indicated that the insoluble protein fraction was more responsible for the observed dough strengthening and mixing tolerance improvement. The responses from consumer sensory study indicated no differences when bread was infused with chickpea flour at 7.5% or below compared to the regular wheat bread. Concluding, roller mill can successfully produce refined pulse flours from whole grains. Compared with other pulse flours, the medium and large-sized lentil flours have better flowing properties comparable to wheat flour. Other pulse flours especially chickpea flours, would need special care to adapt to current grain processing facilities for proper handling and transportation. Comparing the bread-making properties of the pulses, chickpea flours are more suitable for incorporation in refined wheat flour as they produce better bread qualities than lentil and yellow pea flours. The incorporation of chickpea flour in wheat flour showed plainly improved mixing properties and dough strength for the composite flour. The sensory evaluation demonstrated that bread infused with chickpea appropriately is not different from wheat bread alone.
Keywords: Chickpea; Flowability properties; Baking properties; Mixograph and dough extensibility; Sensory; Lentil; Yellow pea